Divergent presentation of anxiety in high-risk groups within the intellectual disability population - Laura Groves; Joanna Moss; Chris Oliver; Rachel Royston; Jane Waite; Hayley Crawford (Journal of Neurodevelopmental Disorders, 2022)
Abstract Background Anxiety symptomatology is common in individuals with intellectual disability (ID). Symptomatology includes both traditional Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) anxiety disorders and autism spectrum disorder (ASD)-related anxiety traits. Some genetic disorders such as Cornelia de Lange (CdLS) and fragile X syndromes (FXS) are at very high risk of anxiety and afford the opportunity to examine prevalence, profiles and associated person characteristics. However, prevalence and associated characteristics of anxiety in these high-risk groups remain poorly described and understood. The aim of the current study was to examine the prevalence and profile of DSM-5 and ASD-related anxiety symptomatology in individuals with CdLS and FXS and associated behavioural and cognitive characteristics. Methods Questionnaires and interviews assessing DSM-5 and ASD-related anxiety were conducted with caregivers of individuals with CdLS (n = 49) and FXS (n = 36). Results DSM-5 anxiety symptomatology was present in both groups with high co-morbidity across anxiety diagnoses. ASD-related anxiety was also prevalent with specific difficulties related to intolerance of uncertainty identified in both groups. Symptomatology was persistent over the lifespan for both groups. Anxiety type was partially associated with repetitive behaviour but not measures of overall ASD phenomenology in CdLS. Conclusions DSM-5 and ASD-related anxiety are common in these high-risk syndromes associated with ID. Prospective syndrome specific presentations and associations, which may implicate specific underlying mechanisms, are discussed. Clinicians should be aware of the risk and difficulties involved in assessment of anxiety in individuals with ID, including atypical types, to ensure these individuals do not “miss” diagnoses and support in general clinical practice.